Drug Information Services at Primary Healthcare, A Study of Patient Satisfaction Analysis among Diabetes Mellitus Patients in Kapanewon Depok Yogyakarta Indonesia - Geraldi Fredrik Daud Tumimbang; Maria Wisnu Donowati (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
Background: Patient satisfaction with drug information services is an important indicator of health services quality.  These services are paramount to diabetes management. They ensure the proper use of medications. The quality of drug information services affects the satisfaction of patients with diabetes. Objectives: This study aimed to evaluate the level of satisfaction among patients with type 2 diabetes mellitus regarding drug information services. Methodology: This observational analytic study used a cross-sectional design. Data were collected using a 21-question questionnaire and interviews based on seven guidelines for providing drug information. The respondents were selected using purposive sampling. The number of them was calculated using the Slovin formula.  Interviews were conducted with pharmacists who provided drug information services. Descriptive statistics were used to analyze the data in this study. Satisfaction analysis in this study used the calculation of the gap between reality and expectations. Result: The respondents were 98 people with type 2 diabetes from Kapanewon Depok Yogyakarta Primary Healthcare who received drug information services. The results indicate that most patients are satisfied with the drug information services at Kapanewon Depok Yogyakarta Primary Healthcare. A dissatisfaction on the right medication found in Depok II.